2016
DOI: 10.1109/tmc.2015.2506583
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Multi-Operator Base Station Deployment Patterns in Cellular Networks

Abstract: Abstract-Stochastic models of base station infrastructure deployment by multiple mobile operators can be an invaluable tool for deriving fundamental results about wireless network sharing. In this paper, we study stochastic geometry models for a shared cellular network consisting of base stations deployed by multiple mobile operators, based on real cellular network data coming from three European countries. Relying on a statistical approach as well as the evaluation of wireless network performance metrics, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 29 publications
0
35
0
Order By: Relevance
“…We also consider an asymptotic case of clustering, i.e., colocation, where the nearest base stations of two operators are located an arbitrarily small distance apart. The clustering case is of particular interest as it is representative of real radio access network deployments, which tend to be deployed to follow social and geographical features, resulting in clustered deployment patterns, see [13], [14].…”
Section: B Our Approach and Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also consider an asymptotic case of clustering, i.e., colocation, where the nearest base stations of two operators are located an arbitrarily small distance apart. The clustering case is of particular interest as it is representative of real radio access network deployments, which tend to be deployed to follow social and geographical features, resulting in clustered deployment patterns, see [13], [14].…”
Section: B Our Approach and Contributionsmentioning
confidence: 99%
“…The key motivation is to analyze the network performance over various realizations of a network consisting of base stations which follow a particular spatial structure. This structure may be expressed as a stochastic model so that the spatial distribution of nodes resembles that of a real radio access network, see, for example, [14], [16]. In particular, we apply the superposition of two homogeneous Poisson point processes (hPPP) [15], to model independently distributed networks, and the Gauss-Poisson process (GPP) [15], to model clustered networks.…”
Section: B Our Approach and Contributionsmentioning
confidence: 99%
“…While a definite answer would require more datasets, the authors of [48] found that base station deployments of different operators in different cities have remarkably similar spatial properties and can be modeled with very similar statistic models. This, along with the fact that we study different demand profiles with different complementarity values, affords to our study a high level of generality.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a few applications dominate others given their relative traffic volume, and applications can be grouped into traffic profiles that describe application usage distribution for any given cell. Other works, e.g., [47], [48] have studied real-world deployments of cellular networks, and found that some spacial features thereof are remarkably similar throughout mobile operators and cities.…”
Section: Related Workmentioning
confidence: 92%
“…Although base station and hotspot infrastructure deployment policies have been widely studied and applied by operators [21], due to the nature of the wireless technologies and their capabilities (e.g., GSM/UMTS/3G/4G and IEEE802.11a,b,g,p), plus the diverse mobility involved (e.g., hotspots for human speed vs. RSUs for vehicular speed), such well-known cellular techniques cannot be applied and/or extrapolated to the RSU domain. Therefore, in this work, we did not consider mobile base station placement models and/or policies.…”
Section: Related Workmentioning
confidence: 99%